Electrical Differentiation of Mesenchymal Stem Cells into Schwann‐Cell‐Like Phenotypes Using Inkjet‐Printed Graphene Circuits. Issue 7 (20th February 2017) - Das, Suprem R.; Uz, Metin; Ding, Shaowei; Lentner, Matthew T.; Hondred, John A.; Cargill, Allison A.; Sakaguchi, Donald S.; Mallapragada, Surya; Claussen, Jonathan C.
Abstract : Graphene‐based materials (GBMs) have displayed tremendous promise for use as neurointerfacial substrates as they enable favorable adhesion, growth, proliferation, spreading, and migration of immobilized cells. This study reports the first case of the differentiation of mesenchymal stem cells (MSCs) into Schwann cell (SC)‐like phenotypes through the application of electrical stimuli from a graphene‐based electrode. Electrical differentiation of MSCs into SC‐like phenotypes is carried out on a flexible, inkjet‐printed graphene interdigitated electrode (IDE) circuit that is made highly conductive (sheet resistance < 1 kΩ/sq) via a postprint pulse‐laser annealing process. MSCs immobilized on the graphene printed IDEs and electrically stimulated/treated (etMSCs) display significant enhanced cellular differentiation and paracrine activity above conventional chemical treatment strategies [≈85% of the etMSCs differentiated into SC‐like phenotypes with ≈80 ng mL −1 of nerve growth factor (NGF) secretion vs. 75% and ≈55 ng mL −1 for chemically treated MSCs (ctMSCs)]. These results help pave the way for in vivo peripheral nerve regeneration where the flexible graphene electrodes could conform to the injury site and provide intimate electrical simulation for nerve cell regrowth. Abstract : Inkjet‐printed graphene circuits induce mesenchymal stem cell differentiation into Schwann cells via solely electrical stimulation. Fluorescent immunolabeling and paracrine activity measurements reveal higher levels of differentiation for cells grown on and electrical stimulated by the graphene circuits versus conventional chemical methods. These results are a step toward the creation of implantable neural network circuits for in vivo stem cell differentiation for neuroregeneration.